The development of libmosaic-sound: a library for sound design and an extension for the Mosaicode Programming Environment - Gonçalves, Luan; Schiavoni, Flávio Luiz (Anais do Simpósio Brasileiro de Computação Musical (SBCM); 2019: Anais do XVII Simpósio Brasileiro de Computação Musical, 2019)
Music has been influenced by digital technology over the last few decades. With the computer, the musical composition could trespass the use of acoustic instruments demanding to musicians and composers a sort of computer programming skills for the development of musical applications. In order to simplify the development of musical applications, several tools and musical programming languages arose bringing some facilities to lay-musicians on computer programming to use the computer to make music. This work presents the development of a Visual Programming Language (VPL) for audio applications in the Mosaicode programming environment, simplifying sound design and making the synthesis and manipulation of audio more accessible to digital artists. It is also presented the implementation of libmosaic-sound library for the specific domain of Music Computing, which supported the VPL development.